High-intensity focused ultrasonic ablation of breast cancer - L. I. Moskvicheva (Исследования и практика в медицине)
Breast cancer is the most frequent and socially signiﬁ cant malignant tumor disease of the female popula on of the Russian Federa on. At present, for the treatment of this pathology, the methods of the organ-preserving surgical manual allowing to achieve the maximum cosme c eﬀ ect along with the observance of the principles of cancer safety are ge  ng more and more developed,. In recent decades, researchers from diﬀ erent countries demonstrate the feasibility and technical safety of various mini-invasive methods of thermal abla on of early stages of breast cancer, characterized by rela ve simplicity of implementa on, excellent cosme c results, short-term rehabilita on of pa ents. These include hyperthermic techniques (radiofrequency, microwave, laser abla on) and hypothermic method (cryoabla on). Each technique has unique characteris cs of impact on the tumor and is performed under the control of ultrasound, computer tomography or magne c resonance imaging. The technical success of these abla on techniques is achieved in 93–98% of cases. Complete tumor necrosis a er radiofrequency abla on is observed in 76–100% of pa ents with breast cancer, laser abla on – in 13–76%, microwave abla on – in 0–8%, cryoabla on – in 36–83%. The frequency of development of speciﬁ c complica ons of local thermal destruc on is 4–13%. To date, there is only one method of noninvasive extracorporeal thermal abla on of tumors of diﬀ erent localiza on – high-intensity focused ultrasound therapy, the eﬀ ec veness and safety of which as a method of local destruc on of benign and malignant tumors of the breast demonstrated by many authors. Like all methods of thermal abla on, high-intensity focused ultrasound therapy has its limita ons, complica ons and disadvantages. This ar cle presents a literary review that highlights the possibili es of this method of local destruc on in pa ents with malignant tumors of the breast.